Peran Filsafat Sains Dalam Pengembangan Pembelajaran Fisika Dasar di FKIP Universitas Jember - Nuraini, Hikmah; Salsabila, Sonia Safira; Widyono, Zakaria; Mahardika, I Ketut; Handono, Sri; Ernasari, Ernasari (Peneliti.net, 2024)
Humans, in essence, will always try to hone the knowledge they have. This is done because of the importance of knowledge in everyday life. Having knowledge will give rise to self-satisfaction in accordance with the times. Studying everything with knowledge is basically a human effort to reach a truth. Truth is a state of something with a real object.